Intra- and inter-species interactions in microbial communities - Luis Raul Comolli (Frontiers Research Topics, 2015)
Recent developments in various "OMICs" fields have revolutionized our understanding of the vast diversity and ubiquity of microbes in the biosphere. However, most of the current paradigms of microbial cell biology, and our view of how microbes live and what they are capable of, are derived from in vitro experiments on isolated strains. Even the co-culturing of mixed species to interrogate community behavior is relatively new. But the majority of microorganisms lives in complex communities in natural environments, under varying conditions, and often cannot be cultivated. Unless we obtain a detailed understanding of the near-native 3D ultrastructure of individual community members, the 3D spatial community organization, their metabolic interdependences, coordinated gene expression and the spatial organization of their macromolecular machines inventories as well as their communication strategies, we won't be able to truly understand microbial community life. How spatial and also temporal organization in cell-cell interactions are achieved remains largely elusive. For example, a key question in microbial ecology is what mechanisms microbes employ to respond when faced with prey, competitors or predators, and changes in external factors. Specifically, to what degree do bacterial cells in biofilms act individually or with coordinated responses? What are the spatial extent and coherence of coordinated responses? In addition, networks linking organisms across a dynamic range of physical constraints and connections should provide the basis for linked evolutionary changes under pressure from a changing environment. Therefore, we need to investigate microbial responses to altered or adverse environmental conditions (including phages, predators, and competitors) and their macromolecular, metabolic responses according to their spatial organization. We envision a diverse set of tools, including optical, spectroscopical, chemical and ultrastructural imaging techniques that will be utilized to address questions regarding e.g. intra- and inter-organism interactions linked to ultrastructure, and correlated adaptive responses in gene expression, physiological and metabolic states as a consequence of the alterations of their environment. Clearly strategies for co-evolution and in general the display of adaptive strategies of a microbial network as a response to the altered environment are of high interest. While a special focus will be placed on terrestrial sole-species or mixed biofilms, we are also interested in aquatic systems, biofilms in general and microbes living in symbiosis. In this Research Topic, we wish to summarize and review results investigating interactions and possibly networks between microbes of the same or different species, their co-occurrence, as well as spatiotemporal patterns of distribution. Our goal is to include a broad spectrum of experimental and theoretical contributions, from research and review articles to hypothesis and theory, aiming at understanding microbial interactions at a systems level.